Radiation field spectra of long-duration cloud flashes - Ahmad, Noor Azlinda (John Wiley and Sons Inc., 2015)
The preliminary results of radiation electric fields produced by long-duration cloud flashes have been Fourier analyzed to determine the frequency spectrum in the range of 10kHz-10MHz. The flashes were recorded within a distance of less than 20km. The spectrum was normalized to 50km distance and it shows a f-1 dependence within the entire frequency range.